EFFECT OF INVESTOR SENTIMENT ON FUTURE RETURNS IN THE NIGERIAN STOCK MARKET - Alajekwu, Udoka Bernard; OBIALOR, Michael Chukwumee; OKORO, Cyprian Okey (Annals of Spiru Haret University. Economic Series, 2017)
The study examined the effect of investor sentiment on future returns in the Nigerian stock market. The OLS regression and granger causality techniques were employed for data analyses. The results showed that (1) investor sentiment has a significant positive effect on stock market returns even after control for fundamentals such as Industrial production index, consumer price index and Treasury bill rate; (2) there is a uni-directional causality that runs from change in investor sentiment (ΔCCI) to stock market returns (Rm). Derived finding showed that the inclusion of fundamentals increased the explanatory power of investor sentiment from 3.96% to 33.05%, though at both level, investor sentiment (ΔCCI) has low explanatory power on stock market returns. The study posits existence of a dynamic relationship between investor sentiment and the behaviour of stock future returns in Nigeria such that higher sentiment concurrently leads to higher stock prices.